ANALISIS NOVEL REFRAIN KARYA WINNA EFENDI DENGAN MENGGUNAKAN PENDEKATAN PSIKOLOGI SASTRA - Sartika Anjelita; A.A. Rai Laksmi; I Komang Widana Putra (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research is a qualitative descriptive study that aims to determine the objective structure and aspects of literary psychology in Winna Efendi's Refrain novel. Data collection was carried out by observing and noting method. The data in this study were processed using content analysis, which is a research technique for objectively, systematically and quantitatively describing the contents of visible communications (manifest). The results of the analysis show that there is an objective structure in the novel Refrain by Winna Efendi in the form of a theme in this novel, namely friendship. The characters in this novel are Nata, Niki, Annalize, Oliver, Helena, Vidia Rossa, Danny, Klaudia, Mama Niki and Vanya. The flow used is the reverse flow. The setting of the place is in the garden next to Nata and Niki's house, Niki's house, school and Nata's house. The time setting is several months ago and night. The atmosphere is happy and empty. The point of view is third person. The message is that true friendship is friendship based on mutual trust, sincerity, and always forgives. There are aspects of literary psychology in the novel Refrain in the form of id, ego and superego. The psychological aspect of literature in Winna Efendi's novel Refrain is that there is an id which is based on the needs and desires of the characters in the novel and they want these needs and desires to be fulfilled on the basis of self-satisfaction. Besides that, there is also an ego, namely the personality of the soul of the characters in Refrain novel, which arises due to environmental factors and relationships with the outside world. The superego in the novel is when the characters realize that their wants and needs do not have to be fulfilled because the characters understand the existence of values and rules that exist within humans.